Fría venganza : el primer caso del sheriff Walt Longmire - Johnson, Craig, 1961- (Nuevos tiempos (Madrid, Spain), 2012)
After decades of peace between the white and Native American communities of early American Wyoming, a young man who was once convicted for raping a Cheyenne girl is found dead, prompting sheriff Walt Longmire, his deputy Victoria Moretti, and friend Henry Standing Bear to investigate.